If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 12 = 28x + -36 Reorder the terms: 12 + 9x = 28x + -36 Reorder the terms: 12 + 9x = -36 + 28x Solving 12 + 9x = -36 + 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28x' to each side of the equation. 12 + 9x + -28x = -36 + 28x + -28x Combine like terms: 9x + -28x = -19x 12 + -19x = -36 + 28x + -28x Combine like terms: 28x + -28x = 0 12 + -19x = -36 + 0 12 + -19x = -36 Add '-12' to each side of the equation. 12 + -12 + -19x = -36 + -12 Combine like terms: 12 + -12 = 0 0 + -19x = -36 + -12 -19x = -36 + -12 Combine like terms: -36 + -12 = -48 -19x = -48 Divide each side by '-19'. x = 2.526315789 Simplifying x = 2.526315789
| 3(x-5)-3=6 | | (T^4/5)^10 | | 0.25x=8x+4 | | -3u-33=2(u-4) | | x+(x+1)+(x+2)=2x-10 | | y=8E-05x+1.4752 | | 5/12=1/4c | | 2x-1+2x+1x+2+4x-3= | | 0.25b=12 | | 7(1+5k)= | | 4x-3+2x-1+x+2+2x+1= | | 3(c+1)= | | 4(2+8x)= | | (3180-x)80.5=1750*x | | 5x+3(x-11)=20x+15 | | 2x+x+3x(2x)=54 | | 2(x+3)+1=11 | | 3(7r+2)= | | 3-[x-3(x-2)]=4 | | 27-7(x-4)+4(2x-3)=0 | | 9(1+u)= | | 7d-2+2=61+2 | | 5x-9x+2=x-5+7 | | 2(2+5m)= | | 2x+36=120 | | 2-4x=5-3(8x+1) | | 10x(2)=6x | | 0.5(x+5)=-4 | | f(13)=2x+6 | | x+40+5x+14=x | | 7+8r+10q-5r-2q+5= | | 50*3+20*4= |